An Analysis The Distinction of Generator and Efficiency Gear Ratio PLTMH Vortex Turbine in Reservoir at Bujel Village - Qidam Agwalul Santoso; Karimatun Nisa; Zainal Abidin; Ulul Ilmi (Merdeka Malang University, 2023)
Energy requirements are needed by modern society in this digital era. Today the most widely used energy is fossil energy. It makes fossil energy can run out at any time. Therefore, alternative energy is needed, especially energy from nature. Indonesia has a lot of potential for the development of hydroelectric power plants. It happens because Indonesia has a tropical climate with very high rainfall and many of rivers with a fairly swift flow. The study done at Bujel village in Ngimbang Sub-District, Lamongan. DC generator is superior because the DC generator used is a low rpm generator, so by low rpm can have a higher voltage level of 25V, while AC generator has a maximum voltage of 11V. Based on the standard level of water turbine efficiency of 70%-90%, it means that the second generator can be said to be efficient because the load used is only a 50 â„¦. The selection of gear ratios also affects the efficiency value of a water turbine because therefore in this study will examine the difference in gear ratios, namely 46:16, 46:18, 46:20. Considering the test results of the three gears, the gear with a ratio of 46:16 has a high rpm level of 468 rpm.